2020
DOI: 10.1086/705331
|View full text |Cite
|
Sign up to set email alerts
|

CEO Behavior and Firm Performance

Abstract: We measure the behavior of 1,114 CEOs in Brazil, France, Germany, India, UK and US using a new methodology that combines (i) data on every activity the CEOs undertake during one workweek and (ii) a machine learning algorithm that projects these data onto scalar CEO behavior indices. Low values of the index are associated with plant visits, and one-on-one meetings with production or suppliers, while high values correlate with meetings with high-level C-suite executives, and several functions together, both from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(67 citation statements)
references
References 47 publications
3
64
0
Order By: Relevance
“…A great deal of research has demonstrated that the competence of a chief executive plays an important role in the market performance of a general enterprise. The ability to navigate the market environment and select the appropriate strategy, managerial ability to acquire and manage the resources necessary for management, and professional and functional skills have been emphasized as essential capabilities of the CEO [20][21][22][23]. In addition, many studies have demonstrated that the CEO's competence not only affects the market performance of ordinary firms, but also the market performance of startups.…”
Section: Literature Review 21 Importance and Capability Of The Ceomentioning
confidence: 99%
“…A great deal of research has demonstrated that the competence of a chief executive plays an important role in the market performance of a general enterprise. The ability to navigate the market environment and select the appropriate strategy, managerial ability to acquire and manage the resources necessary for management, and professional and functional skills have been emphasized as essential capabilities of the CEO [20][21][22][23]. In addition, many studies have demonstrated that the CEO's competence not only affects the market performance of ordinary firms, but also the market performance of startups.…”
Section: Literature Review 21 Importance and Capability Of The Ceomentioning
confidence: 99%
“…However, this does not necessarily reveal all dimensions related to inherent talent and entrepreneurial traits. Bandiera et al (2017) document that owner/manager behaviour and management practices are correlated, and that they are likely to influence aspects of doing business such as credit demand in different ways. Moreover, differences in risk preferences have been linked to both credit demand and firm performance (Cramer et al 2002), and Niederle and Vesterlund (2007) show that gender differences in risk preferences exist that may influence both debt demand and credit constraints.…”
Section: Risk Attitudesmentioning
confidence: 99%
“…While managerial characteristics can be observed through the actual management and business practices, this does not necessarily reveal all relevant information about inherent talent and entrepreneurial traits. Bandiera et al (2017) document that owner/manager behaviour and management practices are correlated, and that they are likely to influence aspects of doing business, such as credit demand, in different ways. Moreover, differences in risk preferences have been linked to both credit demand and firm performance (Cramer et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In line with Shaw (2009) and Ichniowski & Shaw (2012), the surveys cover different types of respondents: store workers, store managers, and the country's general public. Topics include reactions to the ERPs; beliefs about mechanisms for the ERP effects; social perceptions of grocery jobs and our firm; and manager time use (Bandiera et al, 2020).…”
Section: Referral Processmentioning
confidence: 99%